Telecommunications in Asia : Policy, Planning and Development - Harrington, Andrew; Ure, John, 1944- (Book collections on Project MUSE., 1997)
This book provides searching analysis and a detailed and comprehensive account of telecommunications in the developing economies of Southeast and East Asia.